2015
DOI: 10.1556/aphysiol.102.2015.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of left and right ventricular adaptation in endurance-trained male athletes

Abstract: Characteristics of the athlete's heart have been investigated mostly in the left ventricle (LV); reports referring to the right ventricle (RV) have only appeared recently. The aim of the present study was to compare the training effects on RV and LV in elite male endurance athletes. To this end, echocardiography was conducted in 52 elite endurance athletes (A) and in 25 non-athletes (NA). Differences between A and NA in the morphology was more marked in the RV (body-size-matched (rel.)) long axis diastolic dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
4
9
0
3
Order By: Relevance
“…Analysis of diastolic parameters showed significant increase of PFRR in athletes compared to controls. This was driven primarily by lower APFR, which is in line with previously described decrease in A-wave peak velocity in echocardiographic studies [33][34][35]. EPFR did not differ between groups, confirming echocardiographic data on constant E-wave peak velocities [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of diastolic parameters showed significant increase of PFRR in athletes compared to controls. This was driven primarily by lower APFR, which is in line with previously described decrease in A-wave peak velocity in echocardiographic studies [33][34][35]. EPFR did not differ between groups, confirming echocardiographic data on constant E-wave peak velocities [33][34][35].…”
Section: Discussionsupporting
confidence: 89%
“…This was driven primarily by lower APFR, which is in line with previously described decrease in A-wave peak velocity in echocardiographic studies [ 33 35 ]. EPFR did not differ between groups, confirming echocardiographic data on constant E-wave peak velocities [ 33 35 ]. In an echocardiographic study by Santoro et al a significantly higher E/A ratio in endurance athletes was observed, caused by a decrease of the late (atrial) peak diastolic filling velocity [ 33 ].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the right chambers, UT runners showed RV and RA remodeling compared to M runners characterized by increased RV diameters and RA volume in presence of an “enhanced” RV function as indicated by increased RV FAC, TAPSE, RV GLS, RA GCS, and reduced RA GLS. The RV dilation could represent a RV adaption to bradycardia and to the increased venous return, which is associated with increased systolic function, as reported in previous studies (Erol and Karakelleoglu, 2002; D'Andrea et al, 2013; Major et al, 2015). …”
Section: Discussionsupporting
confidence: 61%
“…A sporttevékenységgel kapcsolatos hemodinamikai változások jellegzetes átépülést indukál-nak: a jobb kamra tekintetében főként a dinamikus terhelésű sportágak (például hosszútávfutás, kerékpározás) az üreg dilatációja mellett a kamrafal hypertrophiáját serkentik a bal kamrához hasonlatosan, bár kevésbé kifejezett mértékben [44]. A funkció tekintetében ismert differenciáldiagnosztikai problémát jelent a normáltarto-mány alsó felében lévő vagy enyhén csökkent ejekciós frakció [45].…”
Section: Sportszívunclassified